Corruption, Poverty, and Economic Growth (Causality Studies among Asean Countries) - Yunan, Zuhairan Y.; Andini, Ayu (Universitas Negeri Semarang, 2018)
Corruption has causal impacts on economic and social development indicators. The discussion on this issue is widely interesting among economists, especially in Southeast Asia Countries which have been considered that has as a corrupt governance system. The objective of this study is to analyze the causality of corruption, poverty, and economic growth among ASEAN countries between 2002 and 2015. Four countries have been choosen since they have the same characteristics in term of the indicators presented. Granger causality test and Random Effect Model have been used to answer problem question of this paper. The results show that statistically, both of economic development indicators have a significant effect to corruption, while each indicator has a different direction. Meanwhile, causality test presents a tendency in Philippines. Hence, it is only economic growth is affecting corruption significantly and it occurs between poverty and corruption as well. In Thailand, different result shows that the causality happenes poverty and economic growth indicators. However, Indonesia and Malaysia have no causality at all.